The Effect of Knowledge Level About Chronic Kidney Disease On Psychological Well-Being of Chronic Kidney Disease Patients - Dina Nahdiana; Merry Tiyas Anggraini; Susilo Budi Pratama; Muslimah Muslimah (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background:Chronic kidney disease has emerged as a leading cause of death and suffering in the 21st century. Hemodialysis is the most common renal replacement therapy for patients with chronic kidney disease. Hemodialysis patients experience physical and psychological distress. The psychological effects include increasedFatigue, anxiety, decreased quality of life, and increased risk of suicide are some of the factors contributing to this. Self-acceptance in patients can lead to the development of a new purpose in life, known as psychological well-being. One of the major problems contributing to hemodialysis failure is patient refusal, which is linked to low knowledge. This study aims to analyze the influence of knowledge levels about chronic kidney disease on psychological well-being in patients with chronic kidney disease. Method:This quantitative, observational, and analytical research method utilized a cross-sectional design. A population of 103 patients with chronic kidney disease undergoing hemodialysis in October 2023 served as the study subjects. The sampling technique used was total sampling. The Spearman rank test was also used by the researchers. The research instruments used were a questionnaire on the level of knowledge regarding chronic kidney disease and a questionnaire on the psychological well-being scale theory from Ryf.Results:A total of 89 respondents met the inclusion criteria. The Spearman rank test yielded a p-value of 0.000 and a correlation strength of +0.737, indicating a strong positive effect of knowledge on the psychological well-being of chronic kidney disease sufferers.Conclusion:The better the level of knowledge regarding chronic kidney disease, the greater the impact on improving the psychological well-being of chronic kidney disease sufferers.